2016
DOI: 10.1039/c6ra17706a
|View full text |Cite
|
Sign up to set email alerts
|

Size-controlled synthesis of gold nanoparticles by a novel atmospheric pressure glow discharge system with a metallic pin electrode and a flowing liquid electrode

Abstract: A direct current atmospheric pressure glow discharge operated between a pin-type solid metallic electrode and the surface of a flowing solution, positively or negatively charged and serving as the flowing liquid anode or cathode, was used for synthesizing gold nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 31 publications
0
49
0
Order By: Relevance
“…In this case, modification was done by replacing the mentioned gaseous jet by a pin‐type solid tungsten electrode and stably sustaining dc‐APGD only in surrounding air atmosphere. The developed system with such electrodes arrangement was used for the first time for synthesis of AuNPs and it was found that stable, uniform, and spherical nanostructures could be produced both by irradiation of the flowing liquid electrode solutions of the AuCl4 ions with high‐energy electrons true(enormalgnormalanormalstrue) or positive ions, depending whether they were positively or negatively charged . What is more, it was proved that optical properties, size, and shape of resultant AuNPs could be fully controlled by changing the operating parameters according to the models established in the cited work by design of experiments (DOE) and surface response methodology (SRM) .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this case, modification was done by replacing the mentioned gaseous jet by a pin‐type solid tungsten electrode and stably sustaining dc‐APGD only in surrounding air atmosphere. The developed system with such electrodes arrangement was used for the first time for synthesis of AuNPs and it was found that stable, uniform, and spherical nanostructures could be produced both by irradiation of the flowing liquid electrode solutions of the AuCl4 ions with high‐energy electrons true(enormalgnormalanormalstrue) or positive ions, depending whether they were positively or negatively charged . What is more, it was proved that optical properties, size, and shape of resultant AuNPs could be fully controlled by changing the operating parameters according to the models established in the cited work by design of experiments (DOE) and surface response methodology (SRM) .…”
Section: Introductionmentioning
confidence: 99%
“…Over past few years, a significant interest in new applications of plasma‐liquid interactions (PLIs) has been observed, particularly in relation to their usage in environmental engineering, microbiology, analytical chemistry, and nanotechnology . The use of large quantities of nanomaterials, especially silver (AgNPs) and gold nanoparticles (AuNPs) of well‐defined optical properties and morphology, appears to be necessary nowadays in a broad range of application fields, including medicine, sensing, environmental engineering, and catalysis .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such measures could involve atmospheric pressure plasma (APP) sources of antimicrobial properties due to generated electrons, ions, heat, UV light, electric field, and various active species, and radicals (Ikawa, Kitano, & Hamaguchi, ). APP can be produced with the aid of various sources, including dielectric barrier discharges (DBDs) (Butscher, Van Loon, Waskow, Rudolf von Rohr, & Schuppler, ; Lu, Liu, Song, Zhou, & Niu, ; Miao & Yun, ; Shen et al, ; Tiede, Hirschberg, Viöl, & Emmert, ; Xiong, Roe, Grammer, & Graves, ; Yong et al, ), corona discharges (Kuwahara, Kuroki, Yoshida, Saeki, & Okubo, ; Masaoka, ), radio frequency discharges and plasmas (Akitsu, Ohkawa, Tsuji, Kimura, & Kogoma, ; Laroussi et al, ; Li et al, ; Matan, Puangjinda, Phothisuwan, & Nisoa, ; Ohkawa et al, ), microwave discharges (Gabriel et al, ; Park et al, ), and glow discharges (GD) (Dzimitrowicz et al, ,; Ikawa et al, ). To the best of our knowledge, DBD (Lu et al, ; Tiede et al, ; Xiong et al, ) and radio frequency discharges and plasmas (Laroussi et al, ; Ohkawa et al, ) have been implemented for microbiological and biomedical applications so far.…”
Section: Introductionmentioning
confidence: 99%